Modelling of Ergonomic Risks Factors as predictors to work related fatigue near miss accidents experienced among Malaysian express bus drivers: Partial Least Squares (PLS) Approach - Zahari, Taha; Yusof, Hashim (2016)
Public, stake holders and authorities of Malaysian government show great concern towards high numbers of passenger’s injuries and fatalities in express bus accidents. This paper studies the underlying factors involved in determining the ergonomics risk factors as predictors towards work fatigue related near miss accident. A questionnaire survey was carried out at random among 278 Malaysian express bus drivers at four major cities in peninsular west Malaysia. The result was analyzed by using variance-based Structural Equation Modeling Partial Least Squares (SEM-PLS): Path-analysis approach. The ergonomics risks factors predictors are; sociodemographic, occupation, organizational safety climate, work place environment and occupational stress are empirically tested for the correlation with work related fatigue, musculoskeletal health and near miss accidents. The finding shows that there are significant correlations (socio-demographic, t =7.70; work place environment, t=3.72; occupational, t=2.10) between ergonomics risks factors predictors and work related fatigue. Significant correlations are also observed between work related fatigue and musculoskeletal health (t=10.72) and near miss accident (t=2.09) at significance level, p= 0.1 The study shows that the ergonomic risks factors are significant predictors inducing work related fatigue near miss accident which may influence errors in making critical decision as causation factors on near miss accidents.